Preoperative Predictors of Lymph Node Metastasis in Colon Cancer - Xu, Yansong; Chen, Yi; Long, Chenyan; Zhong, Huage; Liang, Fangfang; Huang, Ling-xu; Wei, Chuanyi; Lu, Shaolong; Tang, Weizhong (Frontiers in Oncology, 2021)
Background: Lymph node metastasis (LNM) is a well-established prognostic factor for colon cancer. Preoperative LNM evaluation is relevant for planning colon cancer treatment. The aim of this study was to construct and evaluate a nomogram for predicting LNM in primary colon cancer according to pathological features. Patients and methods: Six-hundred patients with clinicopathologically confirmed colon cancer (481 cases in the training set and 119 cases in the validation set) were enrolled in the Affiliated Cancer Hospital of Guangxi Medical University from January 2010 to December 2019. The expression of molecular markers (p53 and β-catenin) was determined by immunohistochemistry. Multivariate logistic regression was used to screen out independent risk factors, and a nomogram was established. The accuracy and discriminability of the nomogram were evaluated by consistency index and calibration curve. Results: Univariate logistic analysis revealed that LNM in colon cancer is significantly correlated (P<0.05) with tumor size, grading, stage, preoperative carcinoembryonic antigen (CEA) level, and peripheral nerve infiltration (PNI). Multivariate logistic regression analysis confirmed that CEA, grading, and PNI were independent prognostic factors of LNM (P<0.05). The nomogram for predicting LNM risk showed acceptable consistency and calibration capability in the training and validation sets. Conclusions: Preoperative CEA level, grading, and PNI were independent risk factor for LNM. Based on the present parameters, the constructed prediction model of LNM has potential application value.